Analysis of class I complexity induced spherical polytropic models for compact objects - Malik, Adnan; Mardan, S. A.; Naz, Tayyaba; Khan, Shiraz (Frontiers in Astronomy and Space Sciences, 2023)
In this research, we present a comprehensive framework that uses a complexity factor to analyze class I generalized relativistic polytropes. We establish class I generalized Lane–Emden equations using the Karmarkar condition under both isothermal and non-isothermal regimes. Our approach considers a spherically symmetric fluid distribution for two cases of the generalized polytropic equation of state: 1) the mass density case μo and 2) the energy density case μ. To obtain numerical solutions for both cases, we solve two sets of differential equations that incorporate the complexity factor. Finally, we conduct a graphical analysis of these solutions.